Unraveling obscurins in heart disease - Grogan, Alyssa (Pflugers Arch, 2018)
Obscurins, expressed from the single OBSCN gene, are a family of giant, modular, cytoskeletal proteins that play key structural and regulatory roles in striated muscles. They were first implicated in the development of heart disease in 2007 when two missense mutations were found in a patient diagnosed with hypertrophic cardiomyopathy (HCM). Since then, the discovery of over a dozen missense, frameshift, and splicing mutations that are linked to various forms of cardiomyopathy, including HCM, dilated cardiomyopathy (DCM), and left ventricular non-compaction (LVNC), has highlighted OBSCN as a potential disease-causing gene. At this time, the functional consequences of the identified mutations remain largely elusive, and much work has yet to be done to characterize the disease mechanisms of pathological OBSCN variants. Herein, we describe the OBSCN mutations known to date, discuss their potential impact on disease development, and provide future directions in order to better understand the involvement of obscurins in heart disease.